Indirect Observation of 'Forbidden' Raman Transitions by Laser-Induced Coherence Transfer - Suter, Dieter; Klepel, Harald (EDP Sciences, 1992)
We demonstrate a new spectroscopic technique that makes it possible to obtain information from "forbidden" Raman transitions. The technique, which is based on time-resolved two-dimensional spectroscopy, uses laser-induced transfer of sublevel coherence from the Raman-inactive transition to an allowed Raman transition.
Keywords: 530